Adaptaciones curriculares para mejorar el aprendizaje en niños con discapacidad físicomotriz de preparatoria de la escuela Miguel Riofrío de la ciudad de Loja, periodo académico 2018-2019 - Morocho Chica, Nelly Patricia (2020)
The present thesis evidences the results obtained in the research entitled CURRICULAR ADAPTATIONS TO IMPROVE LEARNING IN CHILDREN WITH PHYSICAL-MOTOR DISABILITIES OF THE HIGH SCHOOL MIGUEL RIOFRIO OF THE CITY OF LOJA, ACADEMIC PERIOD 2018-2019; its general objective is to guarantee the permanence, participation and learning of students with physical-motor disabilities through pedagogical strategies that contribute to improve learning. The literature review addressed topics related to curricular adaptations that seek to modify certain contents to make them more accessible to the student; and, on physical disabilityThe invention relates to a functional condition of the human body which can lead to impossibility or motor difficulty. The methods used in the research were: scientific, descriptive, analytical-synthetic and statistical; in order to obtain information the director of the institution was interviewed, A survey was applied to high school teachers and to children was applied the Portage Guide to Pre-school Education, which tries to evaluate the areas of self-help, motor, socialization, language and cognition. The pre-test showed that 60% of children are in the process of achieving the objectives of the areas, while 40% dominate it. In order to help the development process of the areas in a special way that of motor, a guide to activities was designed and applied called "Include me by my abilities", according to the results obtained it is concluded that 71% of students already dominate the areas; while 29% are in process. Teachers are recommended to use methodologies or strategies for applying curricular adaptations in the classroom, considering one of the most important aspects to improve learning and above all to promote inclusion.